Programmable payments for industry 4.0: a state channel–based trigger solution - Lamberty, Ricky; Kirste, Daniel; Poddey, Alexander (Frontiers in Blockchain, 2025)
The rise of Distributed Ledger Technology (DLT) is revolutionizing financial systems, introducing innovations such as programmable payments, and allowing Machine-to-Machine (M2M) payments, which are essential for Industry 4.0. Despite their potential, DLT-based financial systems face barriers, including operational efficiency, regulatory uncertainty, limited institutional acceptance, and challenges in integrating with conventional financial systems. Trigger solutions emerge as a promising approach to bridge these gaps by combining the programmability and immutability of DLT systems with the regulatory certainty and established trust of conventional financial systems. This work explores key requirements for trigger solutions to support interoperability between DLT-based and conventional financial systems, enabling high-frequency programmable payments and regulatory compliance for industry 4.0. We present a state channel–based trigger solution (SCTS) tailored to meet industry’s requirements, offering a blueprint for integrating advanced payment capabilities into conventional financial systems. SCTS leverages the concept of justified trust-building on technological advantages to enable scalable programmable payments. We find that SCTS enables businesses to adapt to the technological demands of Industry 4.0.